The Quran and the American dream - Films For The Humanities & Sciences (Firm) (Princeton, N.J. : Films for the Humanities & Sciences, 2000)
Discovers the rapid expansion of Islam in New York City, where it sustains and brings hope to Muslim citizens, recent Muslim immigrants, and converts drawn primarily from the downtrodden sectors of society.
Keywords: Islam -- United States; Muslims -- United States